The Good Governance of Schools Under Mukdahan Primary Educational Service Area Office 1 - Kittikanjanasophon, Tarinee; Kiawrat, Anusara (Chophayom Journal, 2025)
This research objectives were: (1) to study The Good Governance of schools under Mukdahan Primary Educational Service Area Office 1; and (2) to compare The Good Governance of schools under Mukdahan Primary Educational Service Area Office 1, classified by educational level and work experience. This research was a survey research. The population was 412 teachers in schools under Mukdahan Primary Educational Service Area Office 1. The sample size of 198 teachers from 34 schools’ academic year of 2023, determined as Krejcie and Morgan’s tables, and by stratified random sampling method. The data collection instrument was five-level rating scale questionnaire. Statistics used in data analysis included frequency, percentage, mean, Standard Deviation, and t-test. The results of the study were found that: (1) The Good Governance Principle of schools under Mukdahan Primary Educational Service Area Office 1, overall was at high level; and (2) comparison of The Good Governance of schools under Mukdahan Primary Educational Service Area Office 1, according to teachers’assessment, classified by educational level and work experience, overall and aspect were not different. Keywords: The Good Governance School, Mukdahan Primary Educational Service Area Office 1